The impact of METTL3 on bladder cancer through m6A modification: a potential therapeutic target and prognostic biomarker - Wen, Dong; Fu, Pengcheng; Shuai, Geliu; Wang, Yuebin; Yu, Shengxin; Liu, Huiquan; Wan, Wei; Zou, Junrong; Zou, Xiaofeng (Frontiers in Oncology, 2025)
Bladder cancer (BCa) is one of the most prevalent malignant tumors globally, particularly among men. According to data from the Global Cancer Research Agency, the annual incidence of BCa continues to rise, and its clinical features are complex, involving various molecular mechanisms and pathophysiological processes. Although existing treatments such as surgery, chemotherapy, and immunotherapy have improved patient prognosis to some extent, many individuals remain at risk for recurrence and metastasis. Therefore, there is an urgent need to explore new biomarkers and therapeutic targets to enhance the diagnostic and therapeutic efficacy of BCa. In recent years, RNA methylation, as an important post-transcriptional modification, has gradually attracted the attention of researchers. Among the methyltransferases, methyltransferase-like 3 (METTL3) is considered a key regulator, which is mainly responsible for the N6-methyladenosine (m6A) modification of mRNA. More and more studies have shown that METTL3 not only plays an important role in normal physiological processes, but also is closely related to the occurrence and development of a variety of tumors. This review aims to systematically explore the role of METTL3 in BCa, including its biological function, expression characteristics, potential therapeutic targets, and prognosis related research progress. Through the in-depth analysis of METTL3, we hope to provide new ideas and directions for the early diagnosis, prognostic evaluation, and the development of novel treatment strategies for BCa.